2019
DOI: 10.3847/1538-4357/ab5115
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping Metallicity Variations across Nearby Galaxy Disks

Abstract: The distribution of metals within a galaxy traces the baryon cycle and the buildup of galactic disks, but the detailed gas phase metallicity distribution remains poorly sampled. We have determined the gas phase oxygen abundances for 7,138 HII regions across the disks of eight nearby galaxies using VLT/MUSE optical integral field spectroscopy as part of the PHANGS-MUSE survey. After removing the first order radial gradients present in each galaxy, we look at the statistics of the metallicity offset (∆O/H) and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
197
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(232 citation statements)
references
References 110 publications
34
197
1
Order By: Relevance
“…We examine the statistical distribution of gas-phase abundances within the ISM of eight nearby (D < 17 Mpc) galaxies. Each galaxy has hundreds to thousands of H II regions with measured 12 + log(O/H) based on strong-line metallicity prescriptions, as observed by the PHANGS-MUSE survey (Kreckel et al 2019; Emsellem et al, in preparation). After fitting and removing a linear gradient in Paper I, we find rms scatter in residual metallicity of 0.04-0.05 dex.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…We examine the statistical distribution of gas-phase abundances within the ISM of eight nearby (D < 17 Mpc) galaxies. Each galaxy has hundreds to thousands of H II regions with measured 12 + log(O/H) based on strong-line metallicity prescriptions, as observed by the PHANGS-MUSE survey (Kreckel et al 2019; Emsellem et al, in preparation). After fitting and removing a linear gradient in Paper I, we find rms scatter in residual metallicity of 0.04-0.05 dex.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…Considering that this only seems to affect sulfur lines, these latter authors suggest that this is due to limitations in stellar atmosphere modeling and/or the atomic data for sulfur. Based on the observation that the discrepancy holds for single H ii regions (from Kreckel et al 2019), Mingozzi et al (2020) exclude the role of diffuse ionized gas as a cause of this issue. However, in our study, we see in Fig.…”
Section: Low Ionization Line Diagnostics: Progress and Caveatsmentioning
confidence: 99%
“…Here, we report on an augmentation of the publicly available SED fitting package CIGALE: Code Investigating GALaxy Emission 1 (Burgarella, Buat & Iglesias-Páramo 2005;Noll et al 2009;Boquien et al 2019) to derive ages, stellar masses, and reddenings for star clusters identified in the Physics at High Angular resolution in Nearby GalaxieS-HST (PHANGS-HST) survey (Lee et al 2021). 2 PHANGS 3 is a panchromatic collaboration comprised of: PHANGS-ALMA, a large CO(2-1) mapping program aimed at covering a representative sample of ∼74 nearby galaxies (Leroy et al, in preparation); PHANGS-MUSE, a Very Large Telescope (VLT) imaging program of ∼20 of the PHANGS galaxies with the MUSE optical integral field unit (IFU) instrument (Emsellem et al, in preparation; see first results in Kreckel et al 2016Kreckel et al , 2019; and PHANGS-HST which aims to chart the connections between molecular clouds and young star clusters/associations throughout a range of galactic environments by imaging the 38 galaxies from the PHANGS sample best suited 4 for study of resolved stellar populations. PHANGS-HST observations, which begun in 2019 April and are scheduled to conclude in mid-2021, are expected to yield NUV-U-B-V-I photometry for tens of thousands of stellar clusters and associations.…”
Section: Introductionmentioning
confidence: 99%